Product and labor market deregulation in unionized oligopoly with asymmetric countries - Hartmut Egger; Frode Meland (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper sets up a general oligopolistic equilibrium trade model for two integrated countries that are similar in all respects except of the prevailing labor market institutions. In one country, the labor market is perfectly competitive, while in the other country labor unions are active in a subset of industries. The differences in labor market institutions are a source of comparative advantage, which crucially impact inter-industry trade and welfare in the open economy. In this setting, we study the trade and welfare implications of labor market deregulation and compare these implications with the consequences of product market deregulation. Thereby, we take into account that labor market reforms are subject to national policy decisions and thus associated with unilateral intervention, while product market deregulation is determined at an international - for instance European - level and thus associated with coordinated intervention in both economies. As a key result, we find that both forms of policy intervention generate a conflict of interest between the two trading partners and that welfare losses materialize for the country with the competitive labor market regime whenever global gains are realized.
Keywords: F12; F16; J51; 330